2014
DOI: 10.1503/cjs.029513
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes of small bowel obstruction in older adult patients: a prospective cohort study

Abstract: Background:The purpose of this research was to examine the morbidity, mortality and rate of recurrent bowel obstruction associated with the treatment of small bowel obstruction (SBO) in older adults. Methods:We prospectively enrolled all patients 70 years or older with an SBO who were admitted to a tertiary care teaching centre between Jul. 1, 2011, and Sept. 30, 2012. Data regarding presentation, investigations, treatment and outcomes were collected. Results:Of the 104 patients admitted with an SBO, 49% were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 34 publications
(40 reference statements)
2
28
3
3
Order By: Relevance
“…Absolute indications for surgery were clinical signs of strangulation, peritonitis, worsening leucocytosis, metabolic acidosis, radiological evidence of bowel ischaemia and failure to progress. Contrary to existing international guidelines suggesting a trial of non‐operative management for up to 3 days, recently published data show that intervention in the first 24–48 h is associated with improved survival . In our study, we have observed a decrease in a number of patients operated 5 or more days after presentation and this may partly account for the demonstrated mortality benefit.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Absolute indications for surgery were clinical signs of strangulation, peritonitis, worsening leucocytosis, metabolic acidosis, radiological evidence of bowel ischaemia and failure to progress. Contrary to existing international guidelines suggesting a trial of non‐operative management for up to 3 days, recently published data show that intervention in the first 24–48 h is associated with improved survival . In our study, we have observed a decrease in a number of patients operated 5 or more days after presentation and this may partly account for the demonstrated mortality benefit.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in keeping with the reported rate of 24–51% in recent studies . Our population included patients with repeated presentation of SBO and over 40% of our patients were over 70 years old – both factors are associated with increase in surgical management . The observed rate of bowel resection in our study is high, but comparable with previously reported .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Postoperative peritoneal adhesion syndrome represents the main cause for the intestinal obstruction in adults 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Postoperative care has evolved significantly over the past few decades with emphasis on a safe, stress free and early recovery of the patients. 9 Conventional postoperative care emphasized resting the gastrointestinal tract until full recovery of function occurs. Prolonged preoperative fasting, use of long acting sedatives, anesthetic agents and opiates, I/V fluids in excess, extended use of drains, nasogastric tubes, urinary catheters, and prolonged nil per oral status all contributed to delayed convalescence after surgery.…”
Section: Introductionmentioning
confidence: 99%